The inexorable passage of time : Images of the Salasaka people through a semiotic perspectivea (Mayéutica Revista Científica de Humanidades y Artes, 2024)
This paper aims to analyze the cultural value of two photographs (past and present images) of the Salasaka Indigenous community, based on the theory of Iuri Lotman. Its importance lies in its cultural value which seeks to rescue the symbolic values of Ecuadorian indigenous communities. The methodology concerns qualitative research approach with specialized support in the “Tartu Semiotics School”. The analyzed sample is intentional, and the selection criteria corresponds to photographic images that represent the changes of social spaces and the Salasaka community. As a substantial conclusion, the researchers consider photographs show a social and cultural vision of the Salasaka community social traits that persist and resist the passage of time.
Keywords: Semiotics; cultural studies; Amerindian culture; Salasaka people